Risk Factors Analysis of Retained Placenta at Regional Public Hospital of Muntilan - Pujiyani, Honesty; Putri, Nindi Pramesthi Vardila; Pujiati, Esthi (Jurnal Kesehatan Komunitas Indonesia, 2023)
About 15 % to 20 % of maternal mortality due to postpartum hemorrhage caused by retained placenta. There are risk factors that lead to retained placenta in labor. The purpose of this study was to determine the risk factors which most influence the incidence of retained placenta. This was observational analytic study with case control study design. The population were all mothers who were treated in Regional Public Hospital of Muntilan at January 2019 to November 2022. The sampling method of case used simple random sampling technique. Data were obtained from medical records. Analysis which used in this study were chi square test. The results showed that there was a significant difference between the spacing of delivery (p-value = 0.004) in the case group and the control group, while the risk factors for age, parity, and history of caesarean section did not show a significant relationship to the incidence of retained placenta (p> 0.05). Delivery interval is a risk factor that influences the incidence of retained placenta in Regional Public Hospital of Muntilan.